Environmental Safeguards in the Construction of Padma Bridge - Ahmed, M Feroze; Ahmed, Tanvir; Rahman, Md Tauhid Ur (MIST International Journal of Science and Technology, 2022)
The Padma Bridge, being the largest infrastructure development project of Bangladesh, required extensive environmental safeguards to make the dream project of Bangladesh environmentally sound. Threat to biodiversity particularly breeding and migration of HIlsha (Tenualosa ilisha) fish, safe disposal of 50 million m3 of dredging spoils, disturbances and displacement of wildlife, conservation of biodiversity, plantation of trees lost to the project, control of construction related noise, air and water pollution, occupational health and safety of the workers were the main environmental impacts of the project. An Environmental Action Plan (EAP) with effective protective measures was successfully implemented. Environmental monitoring of quality of both surface and drinking water, ambient noise level, concentration of PM10, PM2.5, CO, ozone, oxides of nitrogen and sulfur in ambient air, disposal of domestic, construction and hazardous wastes, disposal of dredged spoils, use of personal protective equipment (PPE) and safety at work sites were conducted regularly by a team constituted for this purpose throughout the project period and protective measures were adopted as and when required. Increased flow, water level and temperature in Padma River due to climate change were considered in the design of the Bridge. A wildlife sanctuary has been established in the project area for flourishing of flora and fauna in the protected environment. MIJST, Vol. 10, November 2022 (Special Issue: Padma Bridge): 23-31